Pengaruh Penggunaan Software Eagle Pada Mata Pelajaran Menggambar Teknik Untuk Meningkatkan Hasil Belajar Siswa Kelas X Di SMK Negeri 2 Banda Aceh - Aris Munandar; Hadi Kurniawan; Malahayati Malahayati (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2019)
Based on preliminary observations in the field, from the data, showed that the learning process carried out in class X SMKN 2 Banda Aceh was in accordance with the 2013 curriculum. However, in the learning process there were obstacles namely students' unpreparedness towards the material to be studied. This is caused by the teacher who concerned using the lecture method. As a result, interaction between students and teachers and between students and other students is very less. This is because communication between students and teachers is only one direction, the lack of attention, motivation of students. With the development of science and technology today, the influence of the use of eagle software is expected to improve student learning outcomes. Thus, the formulation of the problems in this study are: 1) How is the effect of using eagle software, in improving student learning outcomes in class X on technical drawing subjects at SMKN 2 Banda Aceh, 2) How are students learning interest with eagle software, on subjects drawing techniques at SMKN 2 Banda Aceh. This research is kind of a classroom action research using quantitative methods. Data was collected through observation and tests. The object of this research is class X students majoring in audio video electronics engineering at SMKN 2 Banda Aceh, totaling 25 students. This research was conducted in two stages. In the first cycle the percentage of observations of student learning activities by 57%, in the second cycle increased to 13% with a percentage value of 70%. This shows that the activeness of student learning in drawing techniques using the use of eagle software has increased in each cycle. Application of the use of eagle software can increase student interest in learning with a percentage of positive responses by 96%, while students with a percentage of negative responses by 4%. The results of the study prove that there is an increase in students' understanding in participating in learning to draw techniques with the use of eagle software.